Dimensi pelaporan kewangan menerusi Internet - Ali Khan, Mohd Noor Azli; Ismail, Noor Azizi (Universiti Utara Malaysia, 2009)
Purpose – This paper aims to address the issue of internet financial reporting(IFR) index, by carefully reviewing existing literature relating to the topic, and then suggests a suitable dimension of disclosure index to represent IFR. Design/Methodology/Approach – The study was dependent on an extensive review of the literature of IFR.Findings – Many have investigated the extent, mode and quality of IFR over the last decade. Most of early IFR research is descriptive and exploratory in nature,thus unable to explain the item to represent the level of IFR. Furthermore,while many have conceded that a suitable proxy such as an index of disclosure can be used to gain insight into the sophistication of information disclosed by companies, to date, very few attempts have been made to develop such index. Of these few studies, the dimensions used to represent IFR are inconsistent among the researchers. These differences contribute to the variations in the findings and thus are unable to clearly explain factors influencing the behaviour of the IFR. Based on extensive literature review, we can conclude that the level of IFR can be categorised into two dimensions, which are content and presentation. Originality/Value – The paper provides a basis for mapping existing and future studies on IFR and constructing scenarios of future studies in this area. Paper type – Conceptual paper.